Brown Adipose Tissue and Novel Management Strategies for Polycystic Ovary Syndrome Therapy - Zhang, Qiaoli; Ye, Rongcai; Zhang, Yuan-Yuan; Fan, Chen-Chen; Wang, Jun; Wang, Shuyu; Chen, Suwen; Liu, Xiaowei (Frontiers in Endocrinology, 2022)
Brown adipose tissue (BAT), a unique tissue, plays a key role in metabolism and energy expenditure through adaptive nonshivering thermogenesis. It has recently become a therapeutic target in the treatment of obesity and metabolic diseases. The thermogenic effect of BAT occurs through uncoupling protein-1 by uncoupling adenosine triphosphate (ATP) synthesis from energy substrate oxidation. The review discusses the recent developments and progress associated with the biology, function, and activation of BAT, with afocus on its therapeutic potential for the treatment of polycystic ovary syndrome (PCOS). The endocrine activity of brown adipocytes affects the energy balance and homeostasis of glucose and lipids, thereby affecting the association of BAT activity and the metabolic profile. PCOS is a complex reproductive and metabolic disorder of reproductive-age women. Functional abnormalities of adipose tissue (AT) have been reported in patients with PCOS. Numerous studies have shown that BAT could regulate the features of PCOS and that increases in BAT mass or activity were effective in the treatment of PCOS through approaches including cold stimulation, BAT transplantation and compound activation in various animal models. Therefore, BAT may be used as a novel therapeutic and/or management strategy for the treatment of patients with PCOS to improve women’s health clinically. It is highly important to identify key brown adipokines for the discovery and development of novel candidates to establish an efficacious therapeutic strategy for patients with PCOS in the future.